2021
DOI: 10.3389/fsurg.2021.667248
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Cochlear Modiolus and Endolymphatic Hydrops in Patients With Menière's Disease

Abstract: Background: Menière's disease (MD) is an inner ear disorder characterized by recurrent episodes of spontaneous vertigo, unilateral low-frequency sensorineural hearing loss, tinnitus, and aural fullness. Current diagnosis still often has to rely on subjective and audiometric criteria only, although endolymphatic hydrops is recognized as the pathophysiological substrate of the disease, having been demonstrated in anatomical pathological studies and by magnetic resonance (MRI). The modiolus has a close functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…The sensitivity and specificity of EHI in terms of MD diagnosis remain controversial. Some studies have reported sensitivities of 100% (24); another have reported a range from 73.2 to 94.2% (21). Specificity is more challenging; this depends on the prevalence of hydrops in normal controls, which is about 10% (25).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of EHI in terms of MD diagnosis remain controversial. Some studies have reported sensitivities of 100% (24); another have reported a range from 73.2 to 94.2% (21). Specificity is more challenging; this depends on the prevalence of hydrops in normal controls, which is about 10% (25).…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, при БМ в эндолимфатическом пространстве происходит задержка калия. Это вызывает калиевую интоксикацию волосковых клеток и вестибулярного нейроэпителия, в результате чего развиваются тугоухость и головокружение [48,49].…”
Section: эпидемиологияunclassified